A novel organic molecule electrode based on organic polymer functionalized graphene for supercapacitor with high-performance. (1st August 2022) - Jiao, Long; Hu, Zhongai; Ma, Fuquan; He, Yuanyuan; Zhou, Qin; Xiao, Liangzhikun; Lv, Liwen; Yang, Yuying
Abstract: Organic synthesis strategy can tune electrochemical behavior of organic molecules by molecular level design, which can offer more material choices for sustainable supercapacitors. Herein, an organic polymer (Poly-perylene-3, 4, 9, 10-tetracarboxydiimide-anthraquinone, PPA) is designed and synthesized as an electrode material that can achieve Faraday reaction with 4 electron transfers in a structural unit. When the PPA is directly used as electrode material, the specific capacitance can be up to 245 F g −1 at 5 mV s −1 within a more negative potential. Furthermore, PPA is modified on reduced graphene oxide (rGO) to prepare an Organic Molecule Electrode (OME, PPA/rGO-1), which can reach higher specific capacitance (604 F g −1 at 5 mV s −1 ) with good cycle stability (capacitance retention of 69.9% at 5 A g −1, over 10, 000 cycles). Besides, a 2, 6-dihydroxynaphthalene (DN) modified graphene hydrogel (GH) is prepared as positive electrode to match with resultant OME for fabricating an asymmetrical supercapacitor (ASC). The device can deliver an energy density of ~20 Wh kg −1 . Two ASCs (in series) light 40 Light Emitting Diodes (LEDs), suggesting a potential application. Graphical abstract: A novel organic polymer (Poly-perylene-3, 4, 9, 10-tetracarboxydiimide-anthraquinone, PPA) is designed and synthesized that can achieve Faraday reaction with 4 electron transfers in a structural unit. Furthermore, PPA is modified on reduced graphene oxide (rGO) to prepare an Organic Molecule Electrode (OME, PPA/rGO-1). A 2, 6-dihydroxynaphthalene (DN) modified graphene hydrogel (GH) is prepared as positive electrode to match with resultant PPA/rGO-1 for fabricating an asymmetrical supercapacitor. The device can deliver an energy density of ~20 Wh kg −1 and present good cycling stability (80%, over 5000 cycles). Two ASCs can light 40 Light Emitting Diodes. Unlabelled Image Highlights: An organic polymer PPA was designed and synthesized as electroactive material. An organic molecule electrode with higher specific capacitance and better cyclic stability was further prepared. The fabricated ACS exhibits good energy storage performance.